(untitled) (Journal of EAHIL, 2020)
This article proposes an analysis on the impact that COVID-19 pandemic is having on the process of scientific publishing in academic journals. It will specifically describe the response of the scholarly publishing community to meet the pressing demand from authors and researchers wishing to disseminate, as rapidly as possible, information on the virus. Its aim is to provide an overview for the community of librarians and information specialists about publishing in the COVID-19 era.